Abbreviated breast magnetic resonance protocol: Value of high-resolution temporal dynamic sequence to improve lesion characterization. Issue 95 (October 2017) - Oldrini, Guillaume; Fedida, Benjamin; Poujol, Julie; Felblinger, Jacques; Trop, Isabelle; Henrot, Philippe; Darai, Emile; Thomassin-Naggara, Isabelle
Abstract: Purpose: To evaluate the added value of ULTRAFAST-MR sequence to an abbreviated FAST protocol in comparison with FULL protocol to distinguish benign from malignant lesions in a population of women, regardless of breast MR imaging indication. Materials and methods: From March 10th to September 22th, 2014, we retrospectively included a total of 70 consecutive patients with 106 histologically proven lesions (58 malignant and 48 benign) who underwent breast MR imaging for preoperative breast staging (n = 38), high-risk screening (n = 7), problem solving (n = 18), and nipple discharge (n = 4) with 12 time resolved imaging of contrast kinetics (TRICKS) acquisitions during contrast inflow interleaved in a regular high-resolution dynamic MRI protocol (FULL protocol). Two readers scored MR exams as either positive or negative and described significant lesions according to Bi-RADS lexicon with a TRICKS images (ULTRAFAST), an abbreviated protocol (FAST) and all images (FULL protocol). Sensitivity, specificity, positive and negative predictive values, and accuracy were calculated for each protocol and compared with McNemar's test. Results: For all readers, the combined FAST–ULTRAFAST protocol significantly improved the reading with a specificity of 83.3% and 70.8% in comparison with FAST protocol or FULL protocol, respectively, without change in sensitivity. By adding ULTRAFAST protocol to FAST protocol, readers 1 and 2 were able to correctly change the diagnosis in 22.9% (11/48) and 10.4% (5/48) of benign lesions, without missing any malignancy, respectively. Both interpretation and image acquisition times for combined FAST-ULTRAFAST protocol and FAST protocol were shorter compared to FULL protocol (p < 0.001). Conclusion: Compared to FULL protocol, adding ULTRAFAST to FAST protocol improves specificity, mainly in correctly reclassifying benign masses and reducing interpretation and acquisition time, without decreasing sensitivity.